Trace gases in the Antarctic Atmosphere - Heidt, L. E.; Pollock, W. H.; Lueb, R. A.; Henry, B. E.; Vedder, J. F. (1989)
Whole-air samples collected aboard the NASA ER-2 and DC-8 aircraft as part of the Airborne Antarctic Ozone Experiment were analyzed in a field laboratory set up at Punta Arenas, Chile. Mixing ratios obtained from gas chromatographic analyses of these samples are presented for CH4, CO, N2O, CFCl3, CF2Cl2, C2F3Cl3, CH3CCl3, and CCl4. A comparison of CFCl3/N2O mixing ratios from the flights of September 16-29, 1987 provides evidence of sustained subsidence.